Respuesta :

Step-by-step explanation:

[tex] (\frac{4x}{y3} ) {}^{ - 2} \\ [/tex]

[tex]( \frac{y {}^{ 3} }{4x} ) {}^{2} \\ [/tex]

[tex]( \frac{y {}^{3 \times 2} }{4x {}^{2} } {}^{} ) \\ [/tex]

[tex] \frac{y {}^{6} }{16x {}^{2} } \\ [/tex]

Answer:

  y^6/(16x^2)

Step-by-step explanation:

The applicable rules of exponents are ...

  (a^b)^c = a^(bc)

  (ab)^c = (a^c)(b^c)

  a^-b = 1/a^b

__

  [tex]\left(\dfrac{4x}{y^3}\right)^{-2}=\dfrac{1}{\left(\dfrac{4x}{y^3}\right)^{2}}=\dfrac{1}{\left(\dfrac{4^2x^2}{y^{3\cdot2}}\right)}=\boxed{\dfrac{y^6}{16x^2}}[/tex]